1984
DOI: 10.1111/j.1365-2222.1984.tb02243.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical symptoms and IgE responses to common food proteins in atopic and healthy children

Abstract: Summary The appearance of symptoms suggestive of allergy through the first 4 years of life was studied prospectively in eighty‐six healthy newborn babies. Blood samples were obtained at birth, at 3,8,25 and 48 months of age and analyzed for levels of total serum IgE and for IgE antibodies to some common foods. The occurrence of IgE antibodies was related to atopic manifestations and to a detailed history of infant feeding and family history of allergy. All infants with elevated cord blood IgE (more than 1.3 kU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
86
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(99 citation statements)
references
References 13 publications
13
86
0
Order By: Relevance
“…In a prospective study, specific IgE to egg white and cow9s milk was found in infants starting from 3 months of age, and reached a peak prevalence at 8 months of age, while IgE for inhalants appeared from 2 yrs of age [18,19]. In this study, the majority of infants received this food early, and IgE responses to this food and to mite allergens were observed at the first measurement, at 6 months of age.…”
Section: Discussionmentioning
confidence: 80%
“…In a prospective study, specific IgE to egg white and cow9s milk was found in infants starting from 3 months of age, and reached a peak prevalence at 8 months of age, while IgE for inhalants appeared from 2 yrs of age [18,19]. In this study, the majority of infants received this food early, and IgE responses to this food and to mite allergens were observed at the first measurement, at 6 months of age.…”
Section: Discussionmentioning
confidence: 80%
“…The detection level was 100 ng/1. Serum IgE levels were determined with Phadebas IgE PRIST® (Pharmacia, Uppsala, Sweden) which was modified to give a lower detection limit of 0.1 kU/l, by prolonging the incubation steps over night [12],…”
Section: Methodsmentioning
confidence: 99%
“…A randomized trial to compare cow's milk with banked human milk in preterm infants reported greater allergic disease in the infants exposed to cow's milk by 18 months of age (194). It is possible that exposure to some food allergens in breast milk increases IgE sensitization (195) and that breast milk itself may increase milk-specific IgE (196), perhaps from the mother's own diet of cow's milk. Thus, maternal diet is an important factor when considering the effect of lactation on atopy (197).…”
Section: The Influence Of Lactation and Dietmentioning
confidence: 99%